Altered Behavior in Encephalitis: Insights From the Australian Childhood Encephalitis Study, 2013–2018 - Burrell, Rebecca; Jones, Cheryl A.; Britton, Philip N.; , The PAEDS Network; Dale, Russell C.; Blyth, Christopher C.; Clark, Julia E.; Crawford, Nigel; Marshall, Helen; Elliott, Elizabeth J.; Macartney, Kristine; Booy, Robert; et al. (Frontiers in Pediatrics, 2021)
Altered mental status is a major criterion for a diagnosis of encephalitis to be made with alteration in behaviour a key manifestation of altered mental status. We reviewed all evaluated cases identified by the Australian Childhood encephalitis study between May 2013 and June 2018, to review the frequency and features of altered behaviour (ALB). ALB was reported in >72% of cases of childhood encephalitis in all three major aetiological groups (infectious, immune-mediated and unknown). The duration of ALB was >7 days in a minority, but significantly more frequent in immune-mediated compared with infectious encephalitis (27% and 10% respectively, p<0.01). ALB was most frequently characterised as irrititability/agitation (47%) which predominated in children aged <1year, and amongst the leading infectious causes in this age group (enterovirus, parechovirus and bacterial meningo-encephalitis). ALB in the form of disorientation/confusion (25%) was most prominent in those aged >1 year and most frequent in immune-mediated encephalitis. Hallucinations, paranoia, aggression were all infrequent; suicidality/self-harm was not observed. ALB was reported in 20 of 21 cases of anti-NMDAr, 19% for >7 days and disorientation/confusion was the most frequent feature. Only one case was reported as presenting with ‘psychosis’ and was diagnosed with anti-NMDAr encephalitis. CONCLUSION: Clinician reported ALB is frequent but most often non-specific in childhood encephalitis. A longer duration of ALB associates with an immune-mediated cause. More specific psychiatric symptoms (hallucinations, paranoia) are very infrequent. Altered behaviour is a hallmark of anti-NMDAr encephalitis, but psychosis is uncommon in contrast to the disorder in adults.